The mathematical specificity device and the production of the subject-teacher-of-mathematics - Grilo, Jaqueline de Souza Pereira; Barbosa, Jonei Cerqueira; Maknamara, Marlécio (Universidade Estadual de Campinas, 2021)
This theoretical essay aims to discuss the mathematical specificity device operated by mathematics teachers. The construction of our argument was based on concepts from the foucaultian toolbox and focused on studies dealing with Mathematical Knowledge for Teaching, the Mathematics Teacher’s Specialized Knowledge of the and Mathematics for Teaching. To problematize the discourse of specific mathematics to teach made it possible to identify the main strength line of the device: the existence of specific mathematics to teach. This, in turn, entangled in the network that constitutes the device produces forms of being-a-teacher-of-Mathematics, within the game of power relations that intends to guide the conduct of these teachers.